2018
DOI: 10.1016/j.meegid.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of Blastocystis subtypes isolated from asymptomatic adults living in Chiang Rai, Thailand

Abstract: Blastocystis is a common and broadly distributed microbial eukaryote inhabiting the gut of humans and other animals. The genetic diversity of Blastocystis is extremely high comprising no less than 17 subtypes in mammals and birds. Nonetheless, little is known about the prevalence and distribution of Blastocystis subtypes colonising humans in Thailand. Molecular surveys of Blastocystis remain extremely limited and usually focus on the central, urban part of the country. To address this knowledge gap, we collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
7
19
0
Order By: Relevance
“…However, ST3 was not the most common subtype in the Indigenous Tapirapé ethnic group in Brazil, which was considered to be related to little contact between indigenous groups and people in other communities [20]. In the present study, three subtypes (ST1, ST3 and ST4) were identified in two ethnic groups, and ST3 was the most common in Yao people (8/12, 66.67%) and in Wa people (5/10, 50%), which was similar to findings previously reported in almost all the studies in China (Table 4) [18,19,41,49,50,[53][54][55][56][57], and in some studies in a nearby country (Thailand) [25,28,37,52]. Minor subtypes (ST5-ST9 and ST12) that are only very rarely found in humans also show differences in geographical distribution.…”
Section: Discussionsupporting
confidence: 86%
“…However, ST3 was not the most common subtype in the Indigenous Tapirapé ethnic group in Brazil, which was considered to be related to little contact between indigenous groups and people in other communities [20]. In the present study, three subtypes (ST1, ST3 and ST4) were identified in two ethnic groups, and ST3 was the most common in Yao people (8/12, 66.67%) and in Wa people (5/10, 50%), which was similar to findings previously reported in almost all the studies in China (Table 4) [18,19,41,49,50,[53][54][55][56][57], and in some studies in a nearby country (Thailand) [25,28,37,52]. Minor subtypes (ST5-ST9 and ST12) that are only very rarely found in humans also show differences in geographical distribution.…”
Section: Discussionsupporting
confidence: 86%
“…Newly acquired sequences belong to ST1, ST2, ST3, ST4, ST5, ST8, ST10, ST14, ST15, and the B. lapemi clade. In agreement with previous studies, ST15, ST16 and ST17 along with sequences originating from ectotherms placed in the (Alfellani et al, 2013;Yowang et al, 2018). Subtypes 3, 4, 8, and 10 grouped together, while subtypes 7, 9 and 6 formed a clade.…”
Section: Phylogenetic Analysissupporting
confidence: 91%
“…Though Blastocystis has been found in individuals with gastrointestinal symptoms, asymptomatic carriage is also common (Scanlan et al, 2014;AbuOdeh et al, 2016;Nieves-Ramirez et al, 2018;Yowang et al, 2018;Mardani Kataki et al, 2019). In vitro experiments using cell lines have shown the invasion potential of some strains/subtypes of Blastocystis (Puthia et al, 2008;Wawrzyniak et al, 2012), with no evidence to date that this also occurs in vivo (Clark et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, ST7 is a relatively common finding in birds (Stensvold et al 2009), suggesting that wild carnivores may acquire Blastocystis by preying on birds carrying the protist. The fact that ST7 has been reported previously in a variety of human populations in Angola, Colombia, or Thailand (Dacal et al 2018;Ram ırez et al 2016;Yowang et al 2018) including Spanish symptomatic individuals (Carmena, unpublished data) indicates that ST7 could be zoonotically transmitted. The finding of ST14 in a fox and a European polecat is interesting, as this Blastocystis subtype has so far been primarily found in production animals (Fayer et al 2012;Li et al 2018) and wildlife members of the family Artiodactyla (Cian et al 2017).…”
Section: Resultsmentioning
confidence: 76%
“…; Yowang et al. ) including Spanish symptomatic individuals (Carmena, unpublished data) indicates that ST7 could be zoonotically transmitted. The finding of ST14 in a fox and a European polecat is interesting, as this Blastocystis subtype has so far been primarily found in production animals (Fayer et al.…”
Section: Resultsmentioning
confidence: 96%